Structure – Property Relationships in Microcrystalline Waxes for Museum Seismic Protection Applications. Issue 4 (November 2015) - Laefer, Debra F.; Kennedy, James E.; O'Flynn, Kevin P.; Stanton, Kenneth T.
The application of microcrystalline waxes to the bases of art objects is an inexpensive method to provide protection from earthquakes and other ground-borne vibrations. In this paper, four microcrystalline waxes that were developed and/or marketed for art object protection are analysed using Fourier transformed infrared spectroscopy, X-ray diffraction, confocal laser scanning microscopy, differential scanning calorimetry, and dynamic rheological analysis. Results from each analysis are compared for each wax and from previously published sources. Findings are considered with respect to previously published mechanical testing performance, in regards to their potential appropriateness for art object protection. In particular, the glass transition temperatures of two of the waxes, as determined by dynamic rheological analysis, are approximately 35°C. This indicates that these two waxes may be unsuitable for museum usage, if ambient temperatures reach these levels.